Outcome-Based Education Curriculum for Arabic Instruction in Islamic Higher Education Institutions - Isop Syafei (Gunung Djati Conference Series, 2026)
This study aims to analyze the integration of the concepts and principles of Outcome-Based Education (OBE) into the Arabic instructional curriculum, formulate and implement learning outcomes, examine the applied teaching and assessment strategies, and evaluate the effectiveness of OBE curriculum implementation in enhancing Arabic language competencies of students in Islamic higher education institutions. This research employs a descriptive qualitative approach to understand the OBE-based Arabic instructional curriculum. Primary data were obtained from lecturers, coordinators, and students, while secondary data came from curriculum documents. Data were collected through interviews, observations, and document studies. Descriptive qualitative analysis involved data reduction, presentation, and conclusion drawing, with triangulation to ensure the validity and reliability of findings. The results indicate that integrating OBE principles into the Arabic curriculum creates a structured learning environment focused on achieving student competencies. Specific and measurable learning outcomes facilitate comprehensive evaluation and active participation through self-reflection. Interactive, collaborative, and project-based learning strategies, supported by authentic assessment, enhance communication, writing, and understanding of Arab-Islamic culture, while strengthening students’ academic competence, character, and professional readiness.